Pharmacokinetics and tolerability of single-dose enteral cannabidiol and cannabidiolic acid rich hemp in horses (Equus caballus) - Thomson, Alexander C. S.; McCarrel, Taralyn M.; Zakharov, Alexander; Gomez, Beatriz; Lyubimov, Alex; Schwark, Wayne S.; Mallicote, Martha F.; Portela, Diego A.; Bisiau, Amber L.; Wakshlag, Joseph J. (Frontiers in Veterinary Science, 2024)
The pharmacokinetics and tolerability of cannabinoids and their metabolites were determined in eight horses after enteral administration of a commercial CBD/CBDA-rich hemp oil product.Each horse was administered 2 mg/kg or 8 mg/kg CBD/CBDA or no treatment in a randomized cross-over design. Serial serum samples collected over 48 hours were analyzed by high performance liquid chromatography with tandem mass spectrometry. Plasma chemistry analysis was performed at 0 hours and 24 hours. Vital parameters, pedometry, and blinded mentation and gait evaluations were recorded at intervals up to 24 hours. Manure production and gastrointestinal transit time were tracked for 48 hours after oil administration.The median maximal concentration of CBD and CBDA were 5.2 and 36.95 ng/mL in the 2 mg/kg group, respectively; and 40.35 and 353.56 ng/mL in the 8 mg/kg group. The median halflife of elimination was not calculated for the 2 mg/kg CBD treatment due to lack of time points above the lower quantifiable limit beyond the Cmax while it was 7.75 hours in the 8 mg/kg group. CBDA absorption was biphasic. Pharmacokinetic parameters for tetrahydrocannabinol, tetrahydrocannabinolic acid, cannabigerolic acid, and 7-carboxy cannabidiol are also reported. No significant differences in any of the measured tolerability parameters were demonstrated between treatment groups. Single-dose enteral administration of CBD/CBDA-rich hemp extract up to 8 mg/kg does not appear to produce neurologic, behavioral, or gastrointestinal effects in horses.